PENERAPAN PENDIDIKAN HOLISTIK BERBASIS KARAKTER DI TAMAN KANAK-KANAK ISLAM BAKTI 24 KOTO GADANG KECAMATAN KOTO BESAR KABUPATEN DHARMASRAYA - isnaini, Isnaini (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Sakinah Dharmasraya, 2020)
The background of this research is TK Islam Bakti 24 Koto Gadang has implemented character based holistic education, but not maximally, the goal in this research is to provide an overview of the implementation of character-based holistic education and the evaluation of character-based holistic education in the TK Islam Bakti 24 Koto Gadang. This type of research is a qualitative descriptive, which is the focus of research that is educators, students and school administrators who are used as data sources. In the collection of data researchers using data sources namely primary data and secondary data, the data collection techniques used are observation, interviews and documentation. Data collection tools are interview guidelines and recording equipment while the data analysis techniques used are data reduction, data presentation and withdrawal of conclusions. Based on the results of the research that has been done can be known that the TK Islam Bakti 24 Koto Gadang has applied a character-based holistic education by dividing the character into nine pillars of character instilled through habituation, transparency, through the story, through songs and by using the book Pillar worksheets. From the observation results and interviews researchers concluded that the TK Islam Bakti 24 Koto Gadang has implemented a character-based holistic education well even though it is not maximized. This is evident with the majority of learners have been good, honest, polite, disciplined, responsible, independent, creative and carry out routine activities such as habituation of worship every day well. But educators are still not maximally applying them, there are educators who have not yet demonstrated good transparency to learners.